Disease Profile of Seizure in Children (TAJ: Journal of Teachers Association, 2018)
This study was done in the Departmen tof Paediatrics, Rajshahi Medical College Hospital, Rajshahi to final out the disease profile of children Hospitalised with seizure presentation. From 01/01/14 to 31/12/14 period a total of 12,560 children in the age group 6 months to 12 years were admitted in the Paediatric department. Among these 656 (5.2%) children were admitted due to convulsion. 62.8% were male and 37.2% female, 53% febrile and 47% a febrile, 59% were less than 5 years. Generalized tonic clonic convulsion (GTC) was the most common seizure type (72.8%). Febrile convulsion, seizure disorder, meningitis and encephalitis were common causes of convulsion.TAJ 2012; 25: 35-37